2002
DOI: 10.1053/jvet.2002.32399
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Comparison of Equine Third Metacarpal Condylar Bone Fragment Compression and Screw Pushout Strength between Headless Tapered Variable Pitch and AO Cortical Bone Screws

Abstract: The 6.5-mm tapered AP screw should provide ample holding strength but would provide less interfragmentary compression than 4.5-mm AO screws for repair of complete lateral condylar fractures in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 17 publications
0
35
1
Order By: Relevance
“…From data supplied by the manufacturer, it has been previously reported that Acutrak-Plus s screws can provide a maximum of 2 mm of compression when inserted to their full length 13 and provided only 44% the compressive force and 65% the compressive pressure of 4.5 mm cortical screws. 14 These investigators found that the compressive force and pressure of Acutrak-Plus s screws compared with 4.5 mm cortical screws was substantially less and more variable (depending on fragment thickness-8, 12, or 20 mm) than in previous reports. 14 Results of this study indicated that compressive force and pressure were greatest in the 8mm-thick fragments owing to the engagement of the finer pitched proximal threads of the Acutrak-Plus s screw in the parent bone.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…From data supplied by the manufacturer, it has been previously reported that Acutrak-Plus s screws can provide a maximum of 2 mm of compression when inserted to their full length 13 and provided only 44% the compressive force and 65% the compressive pressure of 4.5 mm cortical screws. 14 These investigators found that the compressive force and pressure of Acutrak-Plus s screws compared with 4.5 mm cortical screws was substantially less and more variable (depending on fragment thickness-8, 12, or 20 mm) than in previous reports. 14 Results of this study indicated that compressive force and pressure were greatest in the 8mm-thick fragments owing to the engagement of the finer pitched proximal threads of the Acutrak-Plus s screw in the parent bone.…”
Section: Discussionmentioning
confidence: 86%
“…14 These investigators found that the compressive force and pressure of Acutrak-Plus s screws compared with 4.5 mm cortical screws was substantially less and more variable (depending on fragment thickness-8, 12, or 20 mm) than in previous reports. 14 Results of this study indicated that compressive force and pressure were greatest in the 8mm-thick fragments owing to the engagement of the finer pitched proximal threads of the Acutrak-Plus s screw in the parent bone. 31 Like previous studies, we did not remove the articular cartilage from either the distal articular surface of P1 or the proximal articular surface of P2.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The headless design of the AP screw makes it ideal for DIPJ fusion because the entire screw can be successfully buried. Interfragmentary compression studies comparing the AP and 4.5 mm AO cortical bone screw in simulated lateral condylar fractures of equine 3rd metacarpal bone have shown that the AP achieves only 65% of the compressive pressure of the AO screw 11 . For DIPJ arthrodesis, the goal is not to achieve maximal compression, but rather to immobilize the joint (to decrease pain associated with severe degenerative joint disease) as well as to promote more rapid ankylosis; the AP screw accomplishes both objectives by immobilization of the DIPJ joint immediately after screw insertion.…”
Section: Discussionmentioning
confidence: 99%
“…This is unlike traditional AO screws inserted in lag fashion where compression of the fracture relies completely on the screw head. The headless design allows the screw to be positioned beneath the outer cortex which prevents impingement on the overlying tendons, joint capsule, or periosteum and eliminates the need for countersinking in larger fracture fragments 8,14–17 . This design also decreases the likelihood of fragment splitting because there is no screw head applying compression to the fracture fragment 8,14 .…”
Section: Introductionmentioning
confidence: 99%